2012
DOI: 10.1177/2041731412466405
|View full text |Cite
|
Sign up to set email alerts
|

In vitro chondrogenic differentiation of human adipose-derived stem cells with silk scaffolds

Abstract: Human adipose-derived stem cells have shown chondrogenic differentiation potential in cartilage tissue engineering in combination with natural and synthetic biomaterials. In the present study, we hypothesized that porous aqueous-derived silk protein scaffolds would be suitable for chondrogenic differentiation of human adipose-derived stem cells. Human adipose-derived stem cells were cultured up to 6 weeks, and cell proliferation and chondrogenic differentiation were investigated and compared with those in conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 57 publications
5
17
0
Order By: Relevance
“…Spreafico et al (2009) showed that PRP addition in culture 386 medium was proved to increase the proteoglycan production, although the mechanism is still 387 unknown. The result of our research was supported by Kim et al (2012) who observed ADSC 388 differentiation on silk fibroin porous scaffold and showed that ADSC could grow and produce 389 chondrogenic GAG. In comparison to Kim et al (2012), we also evaluated the PRP addition and 390 found that chondrogenic differentiation showed the best when the cells were induced with PRP.…”
Section: Discussionsupporting
confidence: 63%
“…Spreafico et al (2009) showed that PRP addition in culture 386 medium was proved to increase the proteoglycan production, although the mechanism is still 387 unknown. The result of our research was supported by Kim et al (2012) who observed ADSC 388 differentiation on silk fibroin porous scaffold and showed that ADSC could grow and produce 389 chondrogenic GAG. In comparison to Kim et al (2012), we also evaluated the PRP addition and 390 found that chondrogenic differentiation showed the best when the cells were induced with PRP.…”
Section: Discussionsupporting
confidence: 63%
“…Figure 5 and 6 showed the typical cell attachment and growth behaviors on different silk scaffolds. Considering that the excellent cell-compatibility of silk-based scaffolds generally results in over-rapid growth of cells [5456], lower initial cell seeding density was preferred, which resulted in lower cell growth within 6 days. Although the rBMSCs grew well on all the scaffolds from day 1 to day 12, cells formed continuous monolayer on the silk nanofiber-based scaffolds while distributed sparsely on salt-leached scaffolds at day 12 (Figure 6C), indicating the favorable action of nanofiber in cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…AdSCs is currently attracted great interest in the cartilage regeneration since it can differentiate into chondrogenic lineage [23]. The chondrogenic differentiation of ADSCs was observed on the salt leached silk fibroin scaffold, which prepared using traditional dissolution [24]. The scaffolds showed an ability to provide a suitable environment for human adipose-derived stem cells' survival and chondrogenesis.…”
Section: ) Contact Angle and Water Uptakesmentioning
confidence: 99%